Growth and imbalances in Spain: A reassessment of the output gap - Enrique Alberola; Ángel Estrada; Daniel Santabárbara (SERIEs - Journal of the Spanish Economic Association, 2014)
"The Great Recession" was preceded by a prolonged period of high growth accompanied by low and stable inflation, the so called "The Great Moderation". In Spain, a similar pattern was observed: in fact, potential growth estimates were trending upwards, implying that output gaps remained relatively contained. However, the Spanish economy was progressively accumulating other internal and external imbalances. Standard potential growth estimates, which consider inflation as the only indicator of macroeconomic imbalances, therefore provided misleading signals to the policymakers. In this paper we apply to Spain a new methodology to obtain sustainable growth rates, as an alternative measure to potential growth. Sustainable growth is defined as the output growth that does not widen macroeconomic imbalances, identified through a wide set of domestic and external indicators. We find that sustainable growth rates are more stable than potential growth resulting in an output gap that is substantially larger (in absolute value) both before and after the crisis. Another attractive feature of the results is that our measure of output gap turns out to be more robust to revisions than standard measures when 'The Great Recession' emerged.
Keywords: E32; F44; G01; 330; Spain; Sustainable growth; Macroeconomic imbalances; Output gaps; Potential growth